Influence of Foliar Application with Abscisic Acid (ABA) and Vitamin C on Some Plant Hormones for Peas Plant (Pisum sativum L.) - Al-Kaisy, Wifak A; Mahadi, Sahar F (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
A field experiment was conducted at botanical garden of Department of Biology, College of Education for Pure Science (Ibn Al-Haitham), University of Baghdad, during the growth winter season of 2016-2017 to study the effect of different concentrations (0, 10, 20) mg.L-1 of abscisic acid and (0, 50, 100, 150) mg.L-1 of vitamin C and their interaction on some plant hormones of pea plant (Pisum sativum L.). The results showed that ABA 20 mg.L-1 decreased IAA about 27.44%, GA3 about 19.73% and Kinetin 15.37% while vitamin C with 150 mg.L-1 increased IAA 27.43%, GA3 45.31% and Kinetin 58.53%, but ABA increased about 23.01% for ABA and 34.93% for vitamin C compared with control plants. The interaction between them is significant for four plant hormones.